Um sistema imune fuzzy cultural aplicado ao problema de despacho econômico de energia elétrica - Kuk, Josiel Neumann (2009)
The main objective of this work is the proposal of a hybrid system based on Natural Computing approaches, which is capable of efficiently solving different instances of the Economic Load Dispatch problem of electrical energy with valve-point effect. For this purpose it is developed a new approach based on Cultural Algorithm, which has as its population space an Artificial Immune System. In the belief space, we use four knowledge types: situational, normative, topographical and historical. In the communication protocols, the acceptance function is dynamic and the principal influence function is based on a Fuzzy Inference System which defines the probable percentage of application of each knowledge type. Three instances of the Economic Load Dispatch with Non-smooth Cost Functions problem are used to evaluate the proposed paradigm. The results show that the introduction of fuzzy systems to support the decision of which type of knowledge must be applied can bring benefits to the obtained results. Although its parameters were not optimized for each case of study, the proposed algorithm performed likewise the state-of-the-art algorithms.